2003
DOI: 10.1080/1350176032000085379
|View full text |Cite
|
Sign up to set email alerts
|

Path dependency and the CAP

Abstract: Current frameworks for understanding the development of the CAP all suffer from having a static rather than a dynamic perspective. This paper considers whether the concept of path dependency can provide a corrective. However, the large majority of the empirical applications of the concept have been to institutional development at a macro, constitutional level rather than to specific public policies. This paper by defining the CAP as an institution and using the concept of path dependency is an attempt to test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(77 citation statements)
references
References 20 publications
(32 reference statements)
0
73
0
4
Order By: Relevance
“…The concepts of lock-in and path dependency have been recently applied to analyse choices regarding the regulation of rural and urban diffuse pollution (Kirk et al, 2004;Reeves et al, 2007), loss of animal genetic diversity (Tisdell, 2003) and continuing use of pesticides (Vanloqueren and Baret, 2008) illustrating their applicability beyond technology. However, the theory of path dependency has been criticised for its failure to explain change (Kay, 2003). We therefore demonstrate the path dependency characteristics of the farms in our study, but draw primarily on social psychological theory to explain change processes.…”
Section: Analytical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The concepts of lock-in and path dependency have been recently applied to analyse choices regarding the regulation of rural and urban diffuse pollution (Kirk et al, 2004;Reeves et al, 2007), loss of animal genetic diversity (Tisdell, 2003) and continuing use of pesticides (Vanloqueren and Baret, 2008) illustrating their applicability beyond technology. However, the theory of path dependency has been criticised for its failure to explain change (Kay, 2003). We therefore demonstrate the path dependency characteristics of the farms in our study, but draw primarily on social psychological theory to explain change processes.…”
Section: Analytical Approachmentioning
confidence: 99%
“…most efficient or effective) process (North, 1990). Thus a seemingly minor decision can constrain the trajectory of change after that time (Kay, 2003). The concepts of lock-in and path dependency have been recently applied to analyse choices regarding the regulation of rural and urban diffuse pollution (Kirk et al, 2004;Reeves et al, 2007), loss of animal genetic diversity (Tisdell, 2003) and continuing use of pesticides (Vanloqueren and Baret, 2008) illustrating their applicability beyond technology.…”
Section: Analytical Approachmentioning
confidence: 99%
“…A system is path dependent if future choices are canalized by previous decisions into a particular pathway channel and these constraints make it difficult to move forward in a different direction (17). Because of such stabilizing feedback mechanisms, shifting into new pathways might be very difficult.…”
mentioning
confidence: 99%
“…As Grant (2010: 34) The path dependency perspective, as a self-reinforcing force or as a reactive sequence, has also been sought to understand the causes of CAP reform. Pathdependency, which is a key element of historical institutionalism, suggests that 'present structure, or functioning, can only be understood when embedded in a historical perspective' (Daugbjerg, 2009: 395); previous reforms set the direction for future reforms due to large fixed costs, potential network effects, potential learning effects and adaptative expectations (Kay, 2003). This type of analysis has shown that there are links between CAP reforms.…”
Section: Cap Reform Determinants: a Review Of The Literaturementioning
confidence: 99%